TINGKATKAN IMUNITAS TUBUH DIMASA ADAPTASI KEBIASAAN BARU DENGAN DIVERSIFIKASI PRODUK OLAHAN IKAN - Wonggo, Djuhria; Reo, Albert Royke (Media Teknologi Hasil Perikanan, 2021)
The purpose of community service is to strengthten immune system during the adaptation of â€œnew normalâ€, through diversification of processed products to increase the amount of fish consumption and providing B2SA food in the online culinary business for PKK Jaga 6 women in Sea Village, Pineleng District, Minahasa Regency, North Sulawesi Province.Â The method used is counseling, training and mentoring and evaluation.To find out whether the product being offered was accepted by consumers, a hedonic test was conducted on 14 panelists.The diversified products offered are the manufacture of fish kakinaga, fish nuggets and fish Ilobulo. The hedonic test results showed that both the taste, texture, smell and appearance of the fish kakinaga products were between the likes and the most liked and also the most liked. For fish nuggets, consumer acceptance, in terms of taste, texture, smell and appearance, is between very, very fond. Meanwhile, consumer acceptance of Ilobulo fish starts from like to really like. This shows that the three products are very accepted by consumers, especially PKK Jaga 6 women in Sea Village, Pineleng District, Minahasa Regency, North Sulawesi Province.Â